Relationship between the contact load and time-loss injuries in rugby union - Iwasaki, Yusuke; Someya, Yuki; Nagao, Masashi; Nozu, Shojiro; Shiota, Yuki; Takazawa, Yuji (Frontiers in Sports and Active Living, 2024)
Objective Quantifying and managing the matches and training loads of players is important for injury prevention. As rugby union is a full-contact sport and frequent contact injuries occur, it might also be important to quantify and manage players’ contact loads. This study aimed to clarify the relationship between contact load and injury incidence in elite rugby union players. Methods Forty-eight elite rugby union players (27.0 ± 3.5 years) in Japan were monitored during one season (8 months). The contact load, an index of training load, was evaluated as collision count and collision load measured using a global positioning system device, and then calculated using the acute:chronic workload ratio (ACWR) based on the exponentially weighted moving average (EWMA). The association between the EWMA-ACWR of contact load and injury incidence was analyzed using generalized estimating equations. Results Of the 58 injuries during one season, 70.7% were contact injuries. Collision counts and collision load calculated by EWMA-ACWR were associated with the risk of injury (p < 0.01 both), with the odds ratios were 4.20 [95% confidence interval (CI): 1.74–10.11] and 4.44 (95% CI: 1.95–10.13), respectively. Conclusion Contact load calculated using EWMA-ACWR was associated with injury in elite rugby union players.